PKM Pada Masyarakat Kawasan Aditarina Makassar: Jajanan Sehat - Maria Ulfa; Reny Syahruni; Suwahyuni Suwahyuni; Michrun Nisa; Tuti Handayani; Wahyu Hendrarti; Lukman Muslimin; Andi Paluseri; Yuri Pratiwi; Nur Khairi (Jurnal Pengabdian Kefarmasian, 2022)
Dedicated to Community in The Aditarina Makassar: Clean and Healthy Living BehaviorThe area of Aditarania Mosque, Manggala District, Makassar City is an area dominated by the lower middle level community with scavenger professions, there are many school-aged children with low levels of parental knowledge and children on clean and healthy snacks. This service activity aims to provide knowledge and information to the people of the Aditarina region on the importance of consuming healthy snacks. Activities are conducted both offline and audaciously with the lecture and discussion methods. The advice material provided includes the characteristics of healthy snacks, all the harmful ingredients that are often added to snacks, and how to choose healthy snacks. The results of service activities provide the community with increased knowledge about healthy, clean, and safe services.Keywords: Aditarania, snacks, hazardous materials.Kawasan mesjid aditarania Kecamatan Manggala Kota Makassar merupakan kawasan yang didominasi oleh masyarakat tingkat ekonomi menengah kebawah dengan profesi pemulun, terdapat banyak anak-anak usia sekolah dengan tingkat pengetahuan orang tua dan anak yang rendah terhadap jajanan yang bersih dan sehat. Kegiatan pengabdian ini bertujuan untuk memberikan pengetahuan dan informasi kepada masyarakat kawasan Aditarina tentang pentingnya mengkonsumsi jajanan yang sehat. Kegiatan yang dilakukan secara hybrid gabunganluring maupun daring dengan metode ceramah, dan diskusi. Materi penyuluhan yang diberikan meliputi cirri-ciri jajanan yang sehat,bahan-bahan berbahaya apasaja yang sering ditambahakan pada jajanan serta cara memilih jajanan yang sehat. Hasil Kegiatan pengabdian telah memberikan peningkatan pengetahuan kepada masyarakat tentang jajanan yang sehat,bersih dan aman.Kata Kunci : Aditarania,jajanan,bahan berbahaya.